ARAH PENGEMBANGAN BAMBU DI KABUPATEN NGADA: TINJAUAN LITERATUR - Adisa Putra Jaya (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2021)
The approach of sustainable natural resource processing is increasing with the awarening development of global communities and the keys to socio-economic improvement. Bamboo is the types of plants that can be used to fulfill the resource needs and as another alternative to improving the economy engagement in rural creative industries. Bamboo is a well-known plant, especially for rural communities. Ngada is a center development of bamboo in Indonesia, it is because of the abundant potential of bamboo. The utilization of bamboo for the society in Ngada has become as a part of life and has been inherited by their ancestors and can be a focus for economic community development and as promising source of income. The use of bamboo by the society of Ngada in general as a source of household needs so that is an indicator that bamboo is worth more than just a plant. There are further utilization of bamboo that can be divided into: 1) The utilization of upstream subsystem; 2) The utilization of on farm subsystem; 3) The utilization of downstream subsystem, with many utilization areas of bamboo, allows this to be first stage to determining the policy in Ngada that focused on developing of bamboo.